2001
DOI: 10.1046/j.1439-0434.2001.00551.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Influencing the Dispersal of Venturia inaequalis Ascospores in the Orchard Air

Abstract: U. S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…A direct comparison of the two methods in a trial orchard would be necessary to determine how the biosensor compares to qPCR detection limits. In this study, the total number of spores that was found during primary ascospore discharge was comparable to data from a study by Rossi et al (2001), in Northern Italy. Large variation in spore numbers is expected to occur between seasons, due to different environmental conditions leading to spore maturation and discharge (James and Sutton, 1982).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…A direct comparison of the two methods in a trial orchard would be necessary to determine how the biosensor compares to qPCR detection limits. In this study, the total number of spores that was found during primary ascospore discharge was comparable to data from a study by Rossi et al (2001), in Northern Italy. Large variation in spore numbers is expected to occur between seasons, due to different environmental conditions leading to spore maturation and discharge (James and Sutton, 1982).…”
Section: Discussionsupporting
confidence: 87%
“…I8896; SigmaAldrich, St. Louis, MO, US) were used to swab daily spore samples from the VST disc, which were then transferred into 2-ml Eppendorf tubes, and frozen at − 20°C until DNA extraction. The number of ascospores observed per day was corrected for volume of air sampled (4.32 m 3 ) and therefore presents the cumulative average concentration of airborne ascospores m −3 of air, as previously described (Rossi et al 2001).…”
Section: Airborne Apple Scab Inoculum Monitoringmentioning
confidence: 99%
See 3 more Smart Citations